Case Report: Neonatal genital prolapse in a pair of premature Twins - Gu, Jian; Chen, Xiaochun; Li, Shikun; Chen, Wenliang; Zhong, Xinqi (Frontiers in Pediatrics, 2024)
Neonatal genital prolapse is a rare situation. This report presents a unique case involving a pair of premature female twins who both developed vaginal wall prolapse without any neurological deficits. Multiple factors such as selective intrauterine growth restriction, feeding intolerance, extrauterine growth retardation, and elevated intra-abdominal pressure after birth may have contributed to the development of this phenomenon. Notably, the severity of prolapse was more pronounced in the twin with lower birth weight and smaller for gestational age. After a five-month follow-up period, the twins' prolapsed vaginal wall fully retracted due to a combination of conservative treatment and enhanced nutritional support.